D37. Immune Mechanisms in the Lung 2010
DOI: 10.1164/ajrccm-conference.2010.181.1_meetingabstracts.a5740
|View full text |Cite
|
Sign up to set email alerts
|

Gas Signatures From Cultured Human Leukocytes

Abstract: Rationale. The presence of leukocytes in airways indicates substantial inflammation. We wondered whether volatile organic compounds produced by these cells could be detected and ultimately used as noninvasive biomarkers. We recently demonstrated that distinct gases were produced by transformed promyelocitic cells (J. transl Med, 2009 7:31). We hypothesized that neutrophils and peripheral blood mononuclear cells (PBMCs) could generate cell-type specific gases which could be detected even in the parts-per-billio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Exhaled VOCs may also be able to discriminate breath samples by the dominant inflammatory cell type. Cultured white cells both release and use VOCs,9 10 and it is likely that the predominant airway inflammatory cell type will be associated with specific VOC profiles. Non-invasive assessment of metabolites in the breath therefore offers the potential for the discovery of novel biomarkers and for providing insights into inflammatory pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Exhaled VOCs may also be able to discriminate breath samples by the dominant inflammatory cell type. Cultured white cells both release and use VOCs,9 10 and it is likely that the predominant airway inflammatory cell type will be associated with specific VOC profiles. Non-invasive assessment of metabolites in the breath therefore offers the potential for the discovery of novel biomarkers and for providing insights into inflammatory pathways.…”
Section: Introductionmentioning
confidence: 99%
“…How then can we explain the lower levels of aldehydes in the breath of our COPD patients? It may be that the aldehydes in the inhaled air are in fact used as a substrate in the inflammatory process, and indeed neutrophils (the predominant inflammatory cell type in COPD) have been shown to use hexanal in vitro [12]. Basanta et al had also shown similar trend of reproducibility in aldehydes, alkanes and aromatic hydrocarbons [3].…”
Section: Discussionmentioning
confidence: 98%